Metagenomic analysis of DNA viruses from posttransplant lymphoproliferative disorders. (29th January 2019) - Dharnidharka, Vikas R.; Ruzinova, Marianna B.; Chen, Chun‐Cheng; Parameswaran, Priyanka; O'Gorman, Harry; Goss, Charles W.; Gu, Hongjie; Storch, Gregory A.; Wylie, Kristine
Abstract: Posttransplant lymphoproliferative disorders (PTLDs), 50%‐80% of which are strongly associated with Epstein‐Barr virus (EBV), carry a high morbidity and mortality. Most clinical/epidemiological/tumor characteristics do not consistently associate with worse patient survival, so our aim was to identify if other viral genomic characteristics associated better with survival. We extracted DNA from stored paraffin‐embedded PTLD tissues at our center, identified viral sequences by metagenomic shotgun sequencing (MSS), and analyzed the data in relation to clinical outcomes. Our study population comprised 69 PTLD tissue samples collected between 1991 and 2015 from 60 subjects. Nucleotide sequences from at least one virus were detected by MSS in 86% (59/69) of the tissues (EBV in 61%, anelloviruses 52%, gammapapillomaviruses 14%, CMV 7%, and HSV in 3%). No viruses were present in higher proportion in EBV‐negative PTLD (compared to EBV‐positive PTLD). In univariable analysis, death within 5 years of PTLD diagnosis was associated with anellovirus ( P  = 0.037) and gammapapillomavirus ( P  = 0.036) detection by MSS, higher tissue qPCR levels of the predominant human anellovirus species torque teno virus (TTV; P  = 0.016), T cell type PTLD, liver, brain or bone marrow location. In multivariable analyses, T cell PTLD ( P  = 0.006) and TTV PCR level ( P  = 0.012) remained significant. In EBV‐positive PTLD, EBNA‐LP, EBNA1 and EBNA3C had significantly higher levels of nonsynonymous gene variants compared to the other EBV genes. Multiple viruses are detectable in PTLD tissues by MSS. Anellovirus positivity, not EBV positivity, was associated with worse patient survival in our series. Confirmation and extension of this work in larger multicenter studies is desirable. Abstract : We sequenced viral DNA from paraffin‐embedded tissues of PTLD and associated to clinical severity and outcomes. Certain EBV genes had higher proportions of nonsynonymous variants. Anellovirus tissue positivity associated with earlier patient death.